Genomic Imprinting - Bajrami, Emirjeta; Spiroski, Mirko (ID Design 2012/DOOEL Skopje, 2016)
Genomic imprinting is the inheritance out of Mendelian borders. Many of inherited diseases and human development violates Mendelian law of inheritance, this way of inheriting is studied by epigenetics.
Keywords: genomic imprinting; epigenetic inheritance; gene; DNA methylation